2015
DOI: 10.1039/c5ta01183c
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the dispersion of multiwall carbon nanotubes in co-continuous PVDF/ABS blends to design materials with enhanced electromagnetic interference shielding

Abstract: Highly conducting composites were derived by selectively localizing multiwall carbon nanotubes (MWNTs) in co-continuous PVDF/ABS (50/50, wt/wt) blends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(61 citation statements)
references
References 50 publications
3
58
0
Order By: Relevance
“…In our previous study,5 we observed similar effects where MWNTs were preferentially localized in the PVDF phase even when it was blended with the lower viscous and higher surface free energy component(ABS). The SEM micrographs, selective dissolution experiments further support the fact that MWNTs are localized in the PVDF phase.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…In our previous study,5 we observed similar effects where MWNTs were preferentially localized in the PVDF phase even when it was blended with the lower viscous and higher surface free energy component(ABS). The SEM micrographs, selective dissolution experiments further support the fact that MWNTs are localized in the PVDF phase.…”
supporting
confidence: 65%
“…[2][3][4][5] With the aim to circumvent sombre penalties attributable to this interference, shielding of emitted EM radiation has become prime requisite. 1 This emitted EM radiation is a novel kind of effluent, which interferes with the circuitry of nearby appliances and manifests itself as a perturbation in the operation of electronic devices, which, finally can lead to an indecorous operation or malfunction of precise equipments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interfacial energy or the interfacial tension between the components can be calculated from surface energy values using harmonic mean equation and geometric equation. Harmonic mean equation otherwise known as Wu's equation (Equation ) is applicable only for non‐ polar/non‐polar systems and geometric mean or Owens‐Wendt‐Rabel‐Kaelble (OWRK)(Equation ) is applicable for polar/non‐polar systems. PTT is polar and PE is non polar in nature and we have used OWRK equation to calculate interfacial energies of the present system.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Thus, considerable attentions have been devoted to the development of high-performance EMI shielding materials. [7][8][9][10][11][12][13][14][15] The common conductive nanollers are composed of carbon-based nanoparticles like carbon nanobers (CNFs), 7 carbon nanotubes (CNTs) [8][9][10] and graphene nanoplatelets, [11][12][13][14][15] and metal-based nanoparticles like stainless-steel ber, 16 Cu nanowires, 17 silver nanowires (AgNWs) 18,19 and silver nanoplates. [7][8][9][10][11][12][13][14][15] The common conductive nanollers are composed of carbon-based nanoparticles like carbon nanobers (CNFs), 7 carbon nanotubes (CNTs) [8][9][10] and graphene nanoplatelets, [11][12][13][14][15] and metal-based nanoparticles like stainless-steel ber, 16 Cu nanowires, 17 silver nanowires (AgNWs) 18,19 and silver nanoplates.…”
Section: Introductionmentioning
confidence: 99%